ANALISIS PERMINTAAN KB DI PROVINSI SUMATERA BARAT (STUDI KASUS RUMAHTANGGA MISKIN) - Randi Febri Canitra; Melti Roza Adry; Mike Triani (Jurnal Kajian Ekonomi dan Pembangunan, 2019)
This study aims to analyze the impact of (1) UKP (2) Couples Education (3) Respondent Education (4) Family Income (5) Number of Children on the use of family planning in West Sumatra Province. The data analysis tool used is logistic regression using Susenas 2017 data from the Central Statistics Agency (BPS). The study population is households that are married at an early age and already have children. The sample used was 507 poor households categorized using family planning and not using family planning. The hypothesis test used was the G test and the Wald test with a significance level of 5%. The results of the Logistic Regression found that UKP, respondent education, and number of children had an influence on family planning requests in West Sumatra Province. Therefore, equity and development in the field of education should be increased even more, so that education becomes more effective so that later higher quality education will build quality communities. In the long run, it will reduce the problems of poverty and population, especially problems in the growth rate of poor people and households.